Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.35940/ijeat.f1105.0986s319
|View full text |Cite
|
Sign up to set email alerts
|

The Contributions of Reading Strategies and Reading Frequencies Toward Students’ Reading Comprehension Skill in Higher Education

Abstract: This study was conducted because of the low level of students’ reading skill. The reading strategies and the reading frequencies were assumed as the factors affecting students’ reading skill. The aim of this study was to describe and to analyze the contribution of reading strategies and reading frequencies toward students’ reading comprehension skill. This study used the quantitative method with the descriptive correlational design. The population was 3000 students who attended Bahasa Indonesia subject in Univ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…For example, several studies (Tuncer and Bahadir, 2014;Trakhman et al, 2019;Kazazoglu, 2020) indicate that reading is more efficient with better performance in reading comprehension tests in printed texts compared to the same text in digital and according to Spencer (2006) college students prefer to read in print vs. digital texts. In reading the written text, metacognitive strategies are involved (Amril et al, 2019) but studies (Channa et al, 2018) seem to indicate that students do not use them for reading comprehension, specifically; Korotaeva (2012) finds that only 7% of students use them. Concerning the type of text and difficulties, for Wolfe and Woodwyk (2010), expository texts benefit more from the construction of a situational model of the text than narrative texts, although Feng (2011) finds that expository texts are more difficult to read than narrative texts.…”
Section: Introductionmentioning
confidence: 99%
“…For example, several studies (Tuncer and Bahadir, 2014;Trakhman et al, 2019;Kazazoglu, 2020) indicate that reading is more efficient with better performance in reading comprehension tests in printed texts compared to the same text in digital and according to Spencer (2006) college students prefer to read in print vs. digital texts. In reading the written text, metacognitive strategies are involved (Amril et al, 2019) but studies (Channa et al, 2018) seem to indicate that students do not use them for reading comprehension, specifically; Korotaeva (2012) finds that only 7% of students use them. Concerning the type of text and difficulties, for Wolfe and Woodwyk (2010), expository texts benefit more from the construction of a situational model of the text than narrative texts, although Feng (2011) finds that expository texts are more difficult to read than narrative texts.…”
Section: Introductionmentioning
confidence: 99%
“…Another study by Amir focused on the contribution of reading strategies and reading frequencies toward students' reading comprehension skill. The result emphasized awareness of using reading strategies and employment appropriate and effective strategies while dealing with academic texts (Amir et al, 2019). Both studies were conducted in higher education indicated limited studies involving adolescents in Indonesia.…”
Section: ) Grammatical Featuresmentioning
confidence: 99%
“…Academic texts present a new level of lexical difficulty to students as they use specialized writing styles or genres to which many learners may not have been exposed. The last two decades have seen a growing trend toward investigating the importance of reading and teaching different reading strategies to enhance students' reading comprehension (Susanto, 2020;Amir et al, 2019). Though there is little consensus on how many learning strategies are exactly used by learners and how they should be named or grouped.…”
Section: Reading Metacognitive Strategiesmentioning
confidence: 99%